HOSPITAL SERVICE QUALITY AND CUSTOMER TRUST TOWARDS PATIENT SATISFACTION IN GENERATION MZ - Widyarini, Maria; Mogi, Maria Goretti Pracedis; Grahadian, Kevin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
According to Law Number 17 of 2023 of the Republic of Indonesia, health efforts, health resources, and health management are required to improve public health to the highest possible standard. Indonesian hospitals should provide patients with a degree of service excellence as supplied by medical, paramedical, and medical support staff. This research aims to understand, explore, and analyze based on empirically investigating the dimensions or attributes of service quality and evaluate the importance of variance attributes for Gen MZ patients at Hospital B. This quantitative study examines the relationship between service quality and brand trust (independent variable) towards patient satisfaction (dependent variable) in Gen MZ at Hospital B. This research was conducted from January to March 7, 2024; it involved 122 Generation MZ patients using non-probability purposive sampling to represent the population. Result shows that the similar levels of satisfaction and trust between Generations M and Z at Hospital B may be due to the hospital's standardized, high-quality services. This consistency ensures that both generations have comparable experiences. Additionally, Hospital B's effective use of technology, such as hospital apps and online medical information access, meets and exceeds the expectations of both groups.